التغير في كميات الأمطار وتأثيره على إنتاجية القمح في المنطقة الشرقية دراسة في محطة الحسكة خلال الفترة 1991-2010 - هرمز, نور الدين; جلب, أدهم; غضبان, أسامة (Latakia University Journal - Economic and Legal Sciences Series, 2016)
The research aims to study the impact of the change in rainfall on wheat Productivity in al-Hasakah station in the Eastern Province. and to achieve the objectives of the research were to adopt a time series first one from 1991 until 2010,was used and divided by two equal period stretching from 1991 until 2000, and the second period extends from 2001 until 2010, and so on quarterly and annual level for the amount of rain and the productivity of wheat, and Study the effect of rainfall in both periods on wheat production, and the most important results were:1. The results showed that the average wheat production in the first period (1991-2000) was (4.773) t / ha, and in the second period was (4.72) t / ha. It is noted that the average production in the first period was higher than in the second period. but this difference is statistically not significant.2. The results showed that the effect of the change in rainfall on wheat productivity in al-Hasakah station during the first and second periods was positive and statistically significant, The increase of rainfall cause increase in wheat productivity, but the rate of changes in wheat production changes in the first period which associated with change in the rainfall amounts were higher in the first period (69.6%), compared with the second period (50.1%).يهدف البحث إلى دراسة أثر تغير كميات الأمطار على إنتاجية القمح في محطة الحسكة بالمنطقة الشرقية, ولتحقيق أهداف البحث تمّ اعتماد سلسة زمنية تمتد من العام 1991 ولغاية العام 2010, وتقسيمها إلى فترتين متساويتين, الفترة الأولى تمتد من العام 1991 ولغاية العام 2000, والفترة الثانية تمتد من العام 2001 ولغاية العام 2010, وذلك على المستوى الفصلي والسنوي بالنسبة لكميات الأمطار وإنتاجية القمح, ومن ثم دراسة تأثير كميات الأمطار في كلا الفترتين على إنتاجية القمح.وأظهرت النتائج أنّ متوسط إنتاجية القمح في الفترة الأولى (1991-2000) بلغ (4.773) طن/هكتار, وفي الفترة الثانية بلغ (4.72) طن/هكتار, ومن الملاحظ أنّ متوسط الإنتاجية في الفترة الأولى كان أعلى منه في الفترة الثانية إلا أنّ هذا الفرق غير دال إحصائياً.كما أظهرت النتائج أنّ تأثير التغير في كميات الأمطار على إنتاجية القمح في محطة الحسكة خلال الفترتين الأولى والثانية كان موجباً ودالاً إحصائياً, أي بزيادة كميات الأمطار تزداد كمية إنتاجية القمح, إلا أن نسبة التغيرات الحاصلة في إنتاجية القمح في الفترة الأولى والمرتبطة بالتغير في كميات الأمطار كانت أعلى في الفترة الأولى (69.6%), بالمقارنة مع الفترة الثانية (50.1%).